1980
DOI: 10.1161/01.hyp.2.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and hormonal effects of deoxycorticosterone acetate in young pigs.

Abstract: SUMMARY Balances of sodium, potassium, and water were studied in the growing male pig as hypertension developed in response to subcutaneous implantation of deoxycorticosterone acetate (DOCA). Serum sodium, potassium, deoxycorticosterone (DOC), aldosterone, and plasma renln actirity (PRA) were determined. These variables were observed in a total of 10 experimental and nine control pigs. All animals were uninephrectomized and fed a diet of Purina Pig Chow and tap water ad libitum. No salt was added to the food o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 22 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…Therefore, the changes in different parameters among groups were not related with blood pressure or the duration of hypertension. Increased water turnover was described in some of the earliest reports of experimental DOCA hypertension (22). Our study confirms the report of Allan et al (23) who reported that DOCA treated animals consumed more water, on the other hand L-NAME group also had increased water consumption without a significant change in food consumptions.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the changes in different parameters among groups were not related with blood pressure or the duration of hypertension. Increased water turnover was described in some of the earliest reports of experimental DOCA hypertension (22). Our study confirms the report of Allan et al (23) who reported that DOCA treated animals consumed more water, on the other hand L-NAME group also had increased water consumption without a significant change in food consumptions.…”
Section: Discussionsupporting
confidence: 92%
“…The assumption appears to be that in vivo the acetate is rapidly hydrolysed by non-specific esterases to the free alcohol, and hence it is the latter that binds to the receptor. This may well be the case, although it has not been widely verified (Grekin et al 1980). The likely sites of deacetylation and the identities of the enzymes involved would reward study.…”
Section: Beginnings: Isolation and The Bioassay Of Corticosteroidsmentioning
confidence: 99%
“…DOCA salt is a "prototype" model for salt-sensitive hypertension. 4 Secondary renin-angiotensin-aldosterone system suppression, 5 increased secretion of natriuretic peptides, 6 and altered pressure natriuresis 7 establish a new steady state between Na ϩ intake and Na ϩ excretion at a new blood pressure level. The kidneys escape the mineralocorticoid signal, and additional salt retention ceases, albeit with increased blood pressure.…”
mentioning
confidence: 99%